FIGURATIVE LANGUAGES USED IN WILLIAM WORDSWORTH POEMS - Putri, Andini Dwi; Baharuddin, La Sunra; Abdullah, Abdullah (State University of Makassar, 2022)
The purpose of this study is to find out the types of figurative language used in William Wordsworth's poem by using theories from several experts, namely Leech (1969), Perrine (1969), and Kennedy (1995), and to find the meaning contained in the poem. The researchers use qualitative research to describe the types of figurative language found in William Wordsworth's poems and the meaning contained in each of William Wordsworth’s poems. By using the theory of Leech (1969), Perrine (1969), and Kennedy (1995), The researchers will classify the various types of figurative language in William Wordsworth's poems. According to the findings of this research, there are six types of figurative language used in William Wordsworth's poem: personification, simile, metaphor, paradox, hyperbole, and allusion. Personification is a figurative language that is quite widely used in literary works, including in poems, because the literary work or poem will look more attractive, lively, and aesthetic. Similes are often used in poems depending on what the poet wants to convey to the reader. Similes can be used to describe something. Metaphor is one type of figurative language used by William Wordsworth in his poem because this type of figurative language is often used in various literary works that aim to express meaning with an emphasis on the impression the poet wants to convey. In addition, the use of metaphors in a poem can make the words look more alive and interesting to read. A paradox is a type of figurative language that is unique because it can make the reader feel a little confused. This figurative language is used by the poet to express something he does not like or as a subtle rebuke. Hyperbole is one of the most frequently used figures of speech in a literary work, including a poem. The use of this figurative language to compose a sentence by exaggerating something to give the impression that is more than the original. The allusion is a type of figurative language used by William Wordsworth in his poem, its use is to make it easier for readers to understand the meaning of the sentences written by the poet. In addition, its use is to create a reference to suggest the similarity of something through direct reference to commonly known symbols, whether from events, characters, or places. The researchers discovered the meaning contained in the poem after analyzing all of the poems and discovering the types of figurative language used in William Wordsworth's poems. According to the findings of this research, researchers can identify the types of figurative language used in William Wordsworth's poems as well as the meanings contained in each poem. Keywords— Figurative Language, Poem, Semantic